Origin of the Threshold Voltage Shift in a Transistor with a 2D Electron Gas Channel at the Al2O3/SrTiO3 Interface - Taehwan Moon; Hyun Jae Lee; Seung Dam Hyun; Baek Su Kim; Ho Hyun Kim; Cheol Seong Hwang (Advanced Electronic Materials)
Abstract A transistor is fabricated with a 2D electron gas (2DEG) channel at the Al2O3 (AO)/SrTiO3 (STO) interface. The threshold voltage (Vth) shift of the 2DEG channel in the Pt/AO/2DEG/STO stack induced by negative bias stress is investigated. Two‐terminal current–voltage and capacitance–voltage characterization through the gate and the source reveals that the metallic 2DEG channel turns into a semiconducting channel when the negative bias stress is applied. Transfer curve measurement with various stress conditions on the 2DEG field‐effect transistor is performed to evaluate the effect of the negative bias stress. The Vth becomes positive, and the channel conductance decreases after the application of negative bias stress. These variations are promoted by large stress bias and temperature. Electron energy loss spectroscopy analysis via scanning transmission electron microscopy reveals that the chemical state of the interface changes from oxygen‐deficient to stoichiometric. Therefore, the change in the channel state from metallic to semiconducting originates from the decrease of oxygen vacancy concentration at the interface.